DINAMIKA STRUKTUR DAN KOMPONEN PENDIDIKAN : KAJIAN KELEMBAGAAN, SUBSISTEM, DAN PERAN PEMERINTAH DI INDONESIA - Yeni Rahmawati; Robbaniy, Ibrahim; Agus Tinus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The education system is an integrated whole consisting of various interconnected components that work together to achieve national educational goals. This article aims to examine the structure and components of the education system in Indonesia, including the institutional structure of education, the relationships among educational subsystems, and the roles of the government and society in the delivery of education. The method used in writing this article is a literature review of various sources related to the national education system. The results of the study indicate that the education system in Indonesia consists of three main streams—formal, non-formal, and informal education—which complement one another in the process of lifelong learning. In addition, the education system also involves various subsystems such as curriculum, students, educators, facilities and infrastructure, financing, and evaluation, which are interdependent. The implementation of education also requires collaboration between the central government, local governments, and the community to create an effective and high-quality education system.